Effect of Tin Loading on Physical Properties and Phase Transformation of as-synthesized Zn-Sn-O Compound Powder Synthesized by Co-precipitation Method - C. Kahattha; K. Chongsri; R. Noonuruk; W. Mekprasart; W. Pecharapa (My University, 2014)
Zinc-Tin oxide compounds (Zn-Sn-O) were successfully prepared via a facile co-precipitation process using zinc dichloride dihydrate as the zinc source and tin tetrachloride pentahydrate as an additive source. The as-prepared product of Zn-Sn-O powders with various Sn additive contents (0-60%wt) were obtained without calcinations process. The effect of Sn additive on structural and microstructure properties of the samples were characterized by X-ray diffraction(XRD), scanning electron microscope(SEM). The results indicate that the crystallinity and morphologies of ZnO nanoparticles are significantly influenced by Sn additive. The phase formations of Zn-Sn-O including ZnO, ZnSn(OH)6 were observed depending on the Sn-additive composition.
Keywords: Tetrachloride; ZnO doping and properties